Disaster Logistics Management as an Educational Foundation for Disaster Logistics Managers - Yeni Rimadeni; Nasrullah Nasrullah; Afdhal Afdhal; Berwi Fazri Pamudi; Munazar Munazar; Arnisam Arnisam; Erdi Surya (UNIVERSITAS SERAMBI MEKKAH, 2021)
The availability of optimal logistics according to the minimum standards for the needs during the emergency response is crucial in the success of the disaster logistics management series. Logistics supplies with a minimum standard carried out by the Central Aceh District Government are currently not optimal and effective, so disaster logistics planning is needed. With the limitation of the research problem that humanitarian logistics supplies according to the minimum standards for the needs in the initial phase of the emergency response in the face of the landslide disaster in Central Aceh District have not been fulfilled optimally, this study aims to produce optimal and effective efforts to meet the availability of logistics with minimum requirements the right way to do logistics supplies, and how to monitor disaster logistics supplies. All of these things are focused on dealing with the landslide disaster in Central Aceh District. To obtain maximum results this research uses a system consisting of input elements, process elements, and output elements which are supported by primary data and secondary data obtained through in-depth interviews and observations. The results of this study indicate that (1) evaluating several components in the aspect of local government capacity related to logistics supply implementation, (2) Geographically, by analyzing rainfall data, the time is right for carrying out logistics supplies.